The role of China in the Portuguese speaking African countries: The case of Mozambique (Part II) - Ilhéu,Fernanda (2011)
Due to the Reform and Open Door Policies initiated in 1978, China has since recorded rapid and sustainable economic growth, turning it into the worlds second largest economy. With an export oriented economic model, strongly supported by foreign direct investment, China became worlds number one exporter when it overtook Germany in 2009. Presently China has the worlds largest foreign exchange currency funds, 50% of which is being applied in American bonds while the remaining supports Chinese health and social security systems, Chinese banks solvability, internationalization of the Chinese economy, outward foreign direct investment (OFDI) and Chinese official foreign aid (ODA) to other developing countries. Although the Chinese OFDI fluxes are nowadays more oriented to mature economies, the bulk is mainly directed to partnerships with other developing countries like African countries; more specifically, the Chinese government identified the Portuguese Speaking African Countries as strategically important for cooperation and investment. These countries have high expectations of this Chinese investment and cooperation and our research questions are: (a) Should this investment be considered ODA or OFDI?; (b) How far can Chinese finance fluxes contribute to the development of these countries in terms of employment, exports, technology transfer?; (c) Is this investment seen as an opportunity or a threat by local people, is it fulfilling the created expectations or not? Our empirical research concentrates on the Mozambique case in this paper.